Frontispiece: Perylene Diimide‐Based Conjugated Polymers for All‐Polymer Solar Cells. Issue 55 (1st October 2020) - Shi, Qinqin; Wu, Jianfei; Wu, Xiaoxi; Peng, Aidong; Huang, Hui
Abstract : Perylene diimide (PDI)‐based conjugated copolymers demonstrated promising future for polymer solar cells (PSCs) due to their simple structures, easily synthetic routes, and potentially low‐cost manufacture. Read more about the important progress of PDI‐based polymers as non‐fullerene acceptors (NFAs) in all‐polymer solar cells, including the relationship between structures and properties, matching aspects between donors and acceptors, and presented future directions in the Minireview by Q. Shi, A. Peng, H. Huang et al. on page 12510 ff.